THE EFFECT OF AN INTERACTIVE MAP-ASSISTED DISCOVERY LEARNING MODEL ON INTEREST AND LEARNING OUTCOMES OF ELEMENTARY SCHOOL STUDENTS - Zahra, Hayya Fathimah Az; Astuti, Tri (STKIP Citra Bakti, 2026)
This study aims to: (1) analyze the effect of the discovery learning model supported by interactive maps on students’ interest in learning Natural and Social Sciences (NSS); (2) analyze the effect of the discovery learning model supported by interactive maps on learning outcomes in NSS; and (3) analyze the simultaneous effect of the discovery learning model supported by interactive maps on students’ interest and learning outcomes in IPAS. This study employed a quasi-experimental design of the nonequivalent control group type involving 56 fourth-grade students at SDN Ngadirgo 03, comprising an experimental class and a control class. Data were collected through observation, interviews, a learning interest questionnaire, and a learning achievement test. The learning interest questionnaire consisted of 16 valid and reliable Likert-scale statements (Cronbach’s Alpha = 0.883). The learning achievement test consisted of 20 valid and reliable multiple-choice questions (Cronbach’s Alpha = 0.895). The results indicate that: (1) the discovery learning model supported by interactive maps has a significant effect on increasing students’ interest in learning IPAS (sig. 0.000 < 0.05), with an N-Gain of 0.64 (moderate category) in the experimental class, higher than the control class's 0.12 (low category); (2) the discovery learning model supported by interactive maps has a significant effect on improving NSS learning outcomes (sig. 0.000 < 0.05), with an N-Gain of 0.71 (high category) compared to 0.39 (moderate category) in the control class; and (3) based on the MANCOVA test, the model exhibited a significant simultaneous effect on interest and learning outcomes after controlling for pretest scores (sig. 0.000 < 0.05).